Factors associated with variability in the assessment of UK doctors' professionalism: analysis of survey results. (27th October 2011) - Campbell, John L; Roberts, Martin; Wright, Christine; Hill, Jacqueline; Greco, Michael; Taylor, Matthew; Richards, Suzanne
Abstract : Objectives To investigate potential sources of systematic bias arising in the assessment of doctors' professionalism. Design Linear regression modelling of cross sectional questionnaire survey data. Setting 11 clinical practices in England and Wales. Participants 1065 non-training grade doctors from various clinical specialties and settings, 17 031 of their colleagues, and 30 333 of their patients. Main outcome measures Two measures of a doctor's professional performance using patient and colleague questionnaires from the United Kingdom's General Medical Council (GMC). We selected potential predictor variables from the characteristics of the doctors and of their patient and colleague assessors. Results After we adjusted for characteristics of the doctor as well as characteristics of the patient sample, less favourable scores from patient feedback were independently predicted by doctors having obtained their primary medical degree from any non-European country; doctors practising as a psychiatrist; lower proportions of white patients providing feedback; lower proportions of patients rating their consultation as being very important; and lower proportions of patients reporting that they were seeing their usual doctor. Lower scores from colleague feedback were independently predicted by doctors having obtained their primary medical degree from countries outside the UK and South Asia; currently employed in a locum capacity; working as a general practitioner or psychiatrist; being employed in a staff grade, associate specialist, or other equivalent role; and with a lower proportion of colleagues reporting they had daily or weekly professional contact with the doctor. In fully adjusted models, the doctor's age, sex, and ethnic group were not independent predictors of patient or colleague feedback. Neither the age or sex profiles of the patient or colleague samples were independent predictors of doctors' feedback scores, and nor was the ethnic group of colleague samples. Conclusions Caution is necessary when considering patient and colleague feedback regarding doctors' professionalism. Multisource feedback undertaken for revalidation using the GMC patient and colleague questionnaires should, at least initially, be principally formative in nature.